The Integration of Spatial Layouts in the Abdi Dalem Houses in Jeron Beteng, Keraton District, Yogyakarta - Hutomo, Dhemas Aryo; Rahmi, Dwita Hadi (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
The abdi dalem house is a residence built and provided for the royal servants of the Yogyakarta Palace, featuring the traditional Javanese spatial configuration spread throughout the Jeron Beteng area. In recent times, the Jeron Beteng area has undergone significant transformations in response to modern developments, leading to the flexible reconfiguration of spaces to meet contemporary needs. This study aims to examine the evolving spatial patterns in the residences of abdi dalem in the present day. This holds significant importance in understanding the reflections of Javanese vernacular transformation.. The study focuses on two abdi dalem houses in the Panembahan district, known for preserving the original condition of these traditional homes. This qualitative research employs a case study approach, with data collection conducted through purposive sampling, observations, and interviews. Photographic documentation and floor plan sketches were utilized to strengthen the data, alongside literature reviews focusing on cultural, ritual, and traditional aspects of Javanese houses. The study uses two abdi dalem houses that still retain their original façade as case studies. The analysis of spatial integration is performed qualitatively, covering variables such as socio-cultural aspects, spatial layout, building orientation, building functions, land transformation, zoning, spatial circulation, and the integration of spatial patterns. The findings reveal that the integration of spatial patterns in abdi dalem houses for modern-day flexibility is influenced by the evolution of time and the growth of family members. This adaptation occurs without compromising the architectural heritage values of the house, though it does result in changes to the spatial patterns.